Application of genetic modification and genome editing for developing climate-smart banana - Tripathi, L.; Ntui, V.O.; Tripathi, J.N. (Wiley, 2019)
Banana is a major staple food crop feeding more than 500 million people in tropical and subtropical countries. Its production is largely constrained by diseases and pests in addition to other factors such as declining soil fertility, narrow genetic diversity in germplasm, and inadequate availability of clean planting material. The impact of climate change, particularly a rise in temperature and drought, is predicted to affect production adversely due to direct effect on plant agronomy and also influence on pathogens, pests, and their interactions with host plants. There is need to develop climate‐smart varieties of banana with multiple and durable resistance to combat abiotic stresses such as extreme temperature and drought, and biotic stresses such as pathogens and pests. Modern breeding tools, including genetic modification and genome editing, can be applied for the improvement of banana bypassing the natural bottlenecks of traditional breeding. Intensive efforts using genetic modification have been made to develop improved banana varieties with resistance to biotic stresses; however, these need to be coupled with tolerance to abiotic stresses. Genome editing, an emerging powerful tool, can be applied for developing sustainable solutions to adapt to climate change by resisting biotic and abiotic stresses. CRISPR/Cas9‐based genome editing has been lately established for banana, paving the way for functional genomics allowing identification of genes associated with stress‐tolerant traits, which could be used for the improvement of banana for adaptation to a changing climate. This article presents an overview of recent advancements and prospective on the application of genetic modification and genome editing for developing climate‐smart banana.